ChemInform Abstract: Electronic Pseudogap‐Driven Formation of New Double‐Perovskite‐Like Borides within the Sc2Ir6—xTxB (T: Pd, Ni; x: 0—6) Series. Issue 25 (5th June 2015) - Hermus, Martin; Scheifers, Jan P.; Touzani, Rachid; Fokwa, Boniface P. T.
Abstract: DFT calculations for the ternary phases Sc2 M6 B (M: Ir, Pd, Ni) reveal the presence of pseudogaps near their Fermi levels between 61 and 68 valence electrons leading to the prediction of new phases Sc2 Ir6‐x Pdx B and Sc2 Ir6‐x Nix B (x = 0—6) in the double‐perovskite‐like Ti2 Rh6 B‐type structure.